Managing childhood acute lymphoblastic leukemia in a child with Emery-Dreifuss muscular dystrophy - Diptivilasa, Aishvarya; Radhakrishnan, Nita; Verma, Shruti (Asian Journal of Medical Sciences, 2024)
Genetics is increasingly being integrated into clinical oncology practice. It is necessary for risk stratification of disease, for prognostication, for recognition of underlying predisposition, and for recognition of potential toxicity and predicting outcomes. The prevalence of genetic syndromes, their clinical significance, effect on cancer, and its treatment have been defined in recent times. In this present work, we describe the challenges we faced while managing a child with acute lymphoblastic leukemia with an underlying rare muscular dystrophy. The details were recorded from case files and prospectively collected data. Dose modification of certain chemotherapeutic drugs was planned to reduce toxicity in the child. The child responded to treatment and is currently in remission. The recognition of genetic entity and their potential interactions with treatment received for cancer is vital to plan the treatment.